Report of the Council at the opening of the twenty fourth session - SSISI (Statistical and Social Inquiry Society of Ireland, 1871)
The Council have to report the progress of the Society as indicated by the importance and practical character of the papers read and subjects discussed during the past session.
Read Tuesday, 15th November, 1870
Keywords: Minutes of session; Council report; 314.15